Transforming Student Admissions and Curriculum Management Through a Web-Based Application: Transformasi Penerimaan Siswa Baru dan Manajemen Kurikulum Melalui Aplikasi Berbasis Web - Alawiy, Daniel; Suprianto, Suprianto (Indonesian Journal of Law and Economics Review, 2024)
General Background: In the digital era, educational institutions increasingly utilize technology to streamline processes and enhance communication. Specific Background: Darussalam Madrasah Ibtidaiyah, located in Keboguyang Village, Jabon sub-district, Sidoarjo district, has implemented a web-based application for managing new student admissions and storing curriculum data. However, the existing application has limitations, such as the inability to process payments and store student grades. Knowledge Gap: Previous studies have not effectively integrated a comprehensive online admission system with features for curriculum management and data accessibility. Aims: This research aims to design a web-based application that facilitates online student registration, improves document organization, and enhances the ease of teaching and learning activities. Results: The application allows for online registration, eliminating the need for paper forms, while providing accessible information about the school and admission results. Teachers can store and share curriculum data efficiently. Novelty: The proposed system uniquely combines student admission processes with curriculum management, addressing gaps identified in previous research. Implications: This application enhances operational efficiency within the school and improves information access for prospective students and their guardians, ultimately contributing to a more effective educational environment. The integration of user-friendly online tools represents a significant advancement in the management of educational institutions, promoting a modern approach to education. Highlights: Streamlines online student registration and eliminates paper forms. Enhances curriculum data storage and teacher accessibility. Improves communication with prospective parents and guardians. Keywords: web-based application, student admission, curriculum management, educational technology, Darussalam Madrasah